Ekonomi Digital dan Inklusi Keuangan Terhadap Pemulihan Ekonomi Nasional - Murtadlo, Kholid; Sulhan, M. (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
Research aim : This study aims to present or explain the results of a critical review of economic and financial theory used for the National Economic Recovery strategy. Design/Methode/Approach : This study uses a qualitative model with a literature study approach. Research Finding : The digital economy and ecosystem supported by increased financial inclusion are able to accelerate the acceleration of the National Economic Recovery. Theoretical contribution/Originality : This research is also a follow-up study that proves that the financial stimulus of the creative industry sector has shifted to the digital economy with increased financial inclusion in it. Practitionel/Policy implication : Aspects in the digital economy (people, economic, and governance) are one unit to support PEN. Research limitation : The limitation of this research lies in the object of research which is only devoted to PEN in Indonesia, not the ASEAN region.